ANALYSIS OF THE DEVELOPMENT OF THE WORLD MONETARY SYSTEM IN THE PERIOD AFTER THE COVID -19 PANDEMIC (American Journal of Business Management, Economics and Banking, 2023)
The article presents the prospects for the development of the world economy, factors contributing to the transition of the international, regional and national currency systems to a new stage. The basic limitations of the process of development of the global monetary system in post-COVID conditions ( COVID -19 pandemic) are described.